The cities of Crete under Roman rule (1st–3rd centuries AD) - Karambinis, Michalis (Journal of Greek Archaeology, 2022)
This article examines the impact of the increasing connectivity and economic change on Crete after its subjugation to the Romans, to the urban landscape of the island. The study begins with an outline of the economic developments that took place in Crete from the Hellenistic to the Roman imperial period, which affected the urban system(s) of the island; then it continues with a presentation of characteristic case-studies of cities, the archaeological investigation of which offers us adequate evidence; and it concludes with a comprehensive discussion, where an attempt is made to put the evidence from Crete in a broader context.